Analysis of Tariff Policy in The Global Trade War: Its Impact on The Industrial Sector and International Trade - Jumhana, Enjum; Bella, Nilla; Qurba, Harry (Yayasan Education and Social Center, 2025)
The trade war between major economies, particularly the United States and China, has created new dynamics in the global trade system. Tariff policies imposed by these countries have reshaped global supply chains, altered industrial cost structures, and disrupted export–import flows across multiple sectors. This study has aimed to analyze the effects of tariff policies within the context of the trade war on the industrial sector and international trade, and to examine their implications for economic policy strategies in developing economies. A descriptive–comparative method has been employed, utilizing secondary data from international institutions such as the World Bank, IMF, and WTO covering the period 2015–2024. The analysis has focused on the development of tariff levels, export–import values, and the industrial sector’s contribution to gross domestic product (GDP). The findings have shown that protectionist tariff policies have tended to suppress export performance, increase production costs, and widen trade deficits. However, countries that have strengthened industrial productivity and diversified export markets have proven more resilient. These results highlight the importance of adaptive, competitiveness-oriented trade policies amid global uncertainty.